Environmental impact assessment: possible application of the ecomorphic approach - O. M. Kunakh; N. V. Yorkina; Y. O. Zhukova; A. S. Malasay (Agrology, 2020)
Environmental impact assessment (EIA) is a process by which environmental impact information is collected and precautions are determined. In many EIA countries, it is enshrined legislatively, but there is a common problem – in practice, many elements of the procedure are performed at a sub-standardized level. Scientists and practitioners note the problematic nature of the effectiveness of EIA procedures, which is primarily caused by the difficulties of turning assessments of biological diversity into clear management decisions. Biodiversity asses-sment and monitoring programs should consist of a list of protocols that ap-ply reliable methods of accounting for living organisms, taking into account spa-tial and time context. It is particularly noted that without “scientific rigor” and methodology of evaluation, the collected data may not matter for decision-making and represent wasted time and money. The effectiveness of EIA procedures can be improved by incorporating ecosystem services into the concept procedure, as it is a reflection of the functioning of ecosystems, which is a prerequisite for the socio-economic wellbeing of the population. One of the markers of ecosystem services is the ecomorphic structure of living cover. The investigation revealed the role of the ecomorphic structure of the soil macrofauna community as an indicator of the level of anthropogenic effects on the ecosystem. The results indicate that the ecomorphic characteristics of the soil macrofauna community are informative markers of the state of the ecosystem. The soil macrofauna community is divided into functional groups, which should be considered as a mechanism to maintain the stability of the ecosystem as a whole. This structuring has a place in both ecological and geographical space. Comparing grou-ping projections in both of these spaces provides an opportunity to interpret functional groups. It is important to note that both natural and anthropogenic factors structurally affect soil macrofaunf. An important aspect of anthropogenic influence is the inhibition of the endogeic block of the soil macrofauna community. Functionally, it is replaced by an epigeic macrofauna, which is represen-ted by extremely mobile species capable of recolonizing microsites with a temporary reduction in anthropogenic pressure. Thus, the ecomorphic structure of the soil macrofauna community has a high potential for application in the system of environmental impact assessment tools.